The risk of thromboembolic complications due to oral contraception and hormone replacement therapy - Pakalski, Andrzej; Stachowiak, Grzegorz; Połać, Ireneusz; Jędrzejczyk, Sławomir; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Thromboembolic complications in female users of hormone replacement therapy and oral contraception induced the authors to analyze the influence of sex steroids on some haemostatic elements being important in the potential thrombogenic process within the vascular lumen. Presenting the attainable knowledge on this topic, the aim of this paper was, despite the evident rise in the thrombotic risk during the therapy, not to indispose for hormonal therapy, but to pay attention to the fact that by changing the hormonal dose, route or type, this risk can be minimized, making both therapies as safe as possible for menopausal subjects.